Chapter Round Table comment - Unger, Richard W. (Datini Studies in Economic History, 2023)
Trying to comprehend and then to describe the process of technological change and its impact is a difficult task. Explaining it is then extremely demanding. Many of the contributions in the papers offered indicate the value of thick description, of looking closely at relevant documentation, piecing together events from those documents and presenting the information in a comprehensible way. Placing that description within the context of time and place, making the small picture part of the big picture is, after all, doing good history